Practical Rust web projects : building cloud and web-based applications - Lyu, Shing (Apress, 2021)
Go beyond the basics of Rust and build web and serverless cloud applications. The applications explained in this practical book include web sites, RESTful APIs, a real-time web chat application, and frontend application with WebAssembly. Each chapter is organized in the following format: what this kind of application looks like; requirements for the example program; an introduction to the Rust libraries used; step-by-step implementation of the example program, including common pitfalls and best practices; and a brief comparison of libraries and frameworks in the same domain. This book will open your eyes to the world of practical web applications of Rust. After reading the book, you will be able to apply your Rust knowledge to build your own web projects. You will: Build dynamic websites with databases Build RESTful APIs Write a WebSocket server that can power a real-time chat app in Rust Discover the benefits of serverless computing using Amazon Web Service's Rust support Compile Rust to WebAssembly for high-performance frontend applications.